Teaching during the pandemic: The case of Chilean mathematics teachers - Farzaneh Saadati; William Medina-Jerez; Nicole Fuenzalida (OmniaScience, 2023)
This study sought to explore the implementation of remote teaching activities in mathematics classrooms in Chile and its outcomes in this neoliberal country during the COVID-19 pandemic. The challenges that teachers encountered when trying to carry out their remote teaching are also presented. By attending to different types of schools in the Chilean education system, the results of a comparative analysis of frequencies show differences in the use of two options of synchronous and asynchronous teaching activities, software, and in the challenges experienced by the participating teachers from three different school sectors. The results highlight a tendency and flexibility to mix synchronous and asynchronous activities coupled with all available tools from WhatsApp to Zoom. Likewise, findings suggest that the socio-economic segregation in the Chilean education system makes a difference when employing the simple and free access tools by teachers in public schools.